Bottlenecks Detection for Improvement of The Emergency Department Process Flow in A Healthcare Facility - Farhaniz, Nur; Azlina, Nor; Reza, Shahrul; Rohaya, Siti; Anis, Azilah (Advances in Social Sciences Research Journal, 2023)
The emergency room of a healthcare facility is one of the most complicated and challenging service production processes. People often talk about overcrowding, long waiting times for treatment, lower quality and safety of care, as well as ineffective use of resources. It was discovered that delays between diagnosis and treatment are patients’ biggest complaints. Nevertheless, limited studies were found to investigate the causes of delays in the emergency department of a healthcare facility. This study thus aims to investigate how procedures are carried out in the emergency department of a healthcare facility in Klang Valley, particularly to identify the root causes of long waiting times between diagnosis and treatment, as well as to provide some solutions to address the causes. The qualitative method is applied in the present study. Observation and semi-structured interviews with five important internal resource persons/respondents were used to gather the data. The results show that bottlenecks in the Triage Stage, caused by 1) incorrectly classifying a patient’s need, 2) lengthy consultation by a Medical Officer, and 3) a longer time to get the review result of a patient’s admission, cause delays in the emergency department of the Healthcare Facility. The findings discovered that the Healthcare Facility should improve staff-patient communication, establish a more effective Queue Management System (QMS), and reassign duties to improve emergency department process efficiency as well as increase patient satisfaction. The findings from this study, specifically focusing on the comprehensive root-cause analysis, offer the healthcare facility a significant opportunity to drive transformative improvements in patient care and operational efficiency. By leveraging the insights gained through the study, the management can implement the proposed solutions to reduce delays and proactively address emergency department bottlenecks.